Nanofibers as a Vehicle for the Synthetic Attactant TRIMEDLURE to be Used for Ceratitis capitata Wied: (Diptera, Tethritidae) Capture - Bisotto-de-Oliveira, R.; De Jorge, B. C.; Roggia, I.; Sant’Ana, J.; Pereira, C. N. (Journal of Research Updates in Polymer Science, 2014)
Â The Mediterranean fruit fly (medfly), Ceratitis capitata (Wied.) is considered a serious pest of citrus fruits in the southeast of Brazil because of the direct economic impact they have on fruit production and quarantine restrictions for fruit exports. Monitoring and detection of the medfly, using food bait and synthetic attractants, is a key step towards signalling the need for management and control. The aim of this study has been to verify the attractiveness of innovative nanofiber formulations with Trimedlure (TML) for the male of C. capitata in laboratory and field cage tests. Material and Methods: The nanofibers were produced by solution or emulsion electrospinning, containing TML and polymers, such as polycaprolactone, PEG-polycaprolactone, ethyl cellulose and polyvinyl acetate-PVP. Results: At the laboratory the electrophysiological responses were accessed by the eletroanntenogram technique and in the field by the cage test. The bioactivity of C. capitata antennae was highest when stimulated with all TML nanofiber treatments rather than their controls. There were no differences among the TML nanofiber treatments. In the field cages the same number of medflies were found on the adhesive traps baited with one of each of the TML nanofibers.